Reclaiming agency in resident–staff interaction: A case study from a Japanese eldercare facility. (April 2018) - Backhaus, Peter
This article examines the problem of agency in resident–staff interaction in a Japanese eldercare facility. Data were collected during the morning care routines and analysed within the framework of Conversation Analysis. Focusing on the openings and closings, I show that the interactions in the setting under observation are marked by a clear dominance of the care workers. This becomes most obvious at the level of the turn-taking system, where the first pair part of a new sequence is commonly delivered by a care worker, thus assigning a mainly reactive role to the residents. However, the data also contain instances where this pattern is broken up by a reversal of the turn structure. I show how this sequential re-organisation enables a resident to take a more proactive role in determining the relevant next action, arguing that there is much potential for higher resident agency even in routine interactions such as the morning care activities. I also discuss the practical implications of these findings for care communication in general.